2010
DOI: 10.3109/09638237.2010.507683
|View full text |Cite
|
Sign up to set email alerts
|

Employer and employment agency attitudes towards employing individuals with mental health needs

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 23 publications
2
55
0
3
Order By: Relevance
“…Biggs, et al, 2010;Link, et al, 1997;Rosenfield, 1997). However, it seems that perceived stigma alone is enough to impact patient's lives quite dramatically.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…Biggs, et al, 2010;Link, et al, 1997;Rosenfield, 1997). However, it seems that perceived stigma alone is enough to impact patient's lives quite dramatically.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Three-quarters of employers expressed a belief that it would be difficult or impossible to employ someone with schizophrenia (Biggs, Hovey, Tyson, & MacDonald, 2010). Despite patients expressing a desire to work post-discharge from hospital, service providers believed that only 12% of patients were employable .…”
Section: Employmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have indicated the reluctance of employers to hire people with mental illness (Stuart, 2006, McDaid et al, 2005, Biggs et al, 2010, McDaid, 2008. For example, a study in Uganda revealed that an important reason for why people with mental illness are denied access to credit services was that they are believed to have impaired functioning, unable to meaningfully engage in productive work and hence incapable of paying back loans.…”
Section: Income Generation and Employment Opportunitiesmentioning
confidence: 99%